Local Property Tax Limitations vs. School District Employee Pension Costs in Pennsylvania - William T. Hartman; Timothy J. Shrom (Educational Considerations, 2014)
In Pennsylvania as in many other states, employee pension costs are a significant source of financial pressure for school districts. In order to gain greater insight into the nature of Pennsylvania school districts’ financial burden related to pension commitments, this article presents the findings of two scenarios, one which compared the maximum amount of local property tax revenue Pennsylvania school districts could raise under a 2010 state property tax limitation statute, Act 120, to their pension obligations; and a second scenario which incorporated a 1% annual salary increase into the analysis. The article is divided into three sections.
Keywords: employee pension; analysis; Pennsylvania; school districts; budgets; challenges; property tax; expenditure; data source; Department of Education; balance